Surface-enhanced raman scattering substrate having no metal nanoparticles, and method for manufacturing the same
Patent Information
- Application Number
- JP2023191204
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-25
- Filing Date
- 2023-11-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-11-09
AI Technical Summary
【0026】 本発明のSERS基板は、金属ナノフィルムを用いることにより、表面プラズモン共鳴が生じる構造を形成し、レーザー照射による金属ナノ粒子の形やピッチの変化を避け、SERS基板の安定性、再現性、均一性を向上させることができる。
Smart Images

Figure 2025031442000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface-enhanced Raman scattering substrate free of metal nanoparticles and a method for manufacturing the same, in particular to a surface-enhanced Raman scattering substrate including an anodic alumina substrate having a three-dimensional hole structure and a metal nanofilm on the anodic alumina substrate, and a method for manufacturing the same. [Background technology]
[0002] Surface Enhanced Raman Scattering (SERS) is a spectroscopic technique that allows for rapid, non-destructive, and non-contact optical analysis of the molecular bonds of the specimen. SERS uses laser excitation of precious metals attached to micron- or nano-scale surface structures to produce the surface plasmon resonance phenomenon. When the laser is irradiated, a local electromagnetic field is generated, which causes charge separation on the local surface of the metal, amplifying the Raman signal. Therefore, it is widely used in the fields of analytical science, material physics, and biomedicine. SERS technology has characteristics such as high sensitivity, non-destructiveness, and the ability to directly test liquid samples, making it a highly potential analytical tool that is used in agricultural research, environmental testing, molecular biology testing, and medical health care.
[0003] In conventional SERS technology, metal nanoparticles such as silver or gold particles are used as a method for Raman enhancement, but metal nanoparticles are difficult to control, and in addition, when irradiated with a laser, their shape and pitch are easily changed. Therefore, conventional SERS substrates have poor reproducibility and uniformity. China Patent CN102621122A discloses a method for improving the detection ability of SERS by depositing multiple nano-level metal particles at the bottom of the holes of a porous anodic alumina film using electroplating. However, this patented technology not only has a complex process, but also requires acid wet etching or destruction of the alumina barrier layer, which may cause environmental pollution. In addition, because nano-level metal particles are used, SERS substrates have poor reproducibility and uniformity.
[0004] Anodic Aluminum Oxide (AAO) is a porous nanomaterial. Compared with using silicon, glass, or polymeric materials as substrates, AAO eliminates the need for complex and costly lithography and etching processes to fabricate SERS substrates.
[0005] According to Taiwan Patent Publication No. I731600, the SERS substrate made using the AAO substrate can improve the SERS detection ability because the electric field is enhanced along the nanopores of the AAO. However, although the SERS substrate with the two-dimensional AAO substrate has an enhancing effect, the detection ability is still insufficient for the detection of extremely low concentration samples, and there are still difficulties in its application.
[0006] For these reasons, many studies have been conducted on SERS substrates, but the current industry demands SERS substrates that have a simpler manufacturing process, are lower cost, are contamination-free, have high reproducibility, high uniformity, and can detect even extremely low concentrations of substances (i.e., have higher detection capabilities). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Taiwan Patent Publication No. I731600 Summary of the Invention [Problem to be solved by the invention]
[0008] In view of the above, the present invention aims to provide a SERS substrate without metal nanoparticles and a manufacturing method thereof, which provides a simpler, lower-cost, and non-contaminating process. The SERS substrate manufactured by the process has a three-dimensional pore structure of AAO substrate, can detect even very low concentrations of substances, and has high reproducibility and uniformity. [Means for solving the problem]
[0009] The SERS substrate of the present invention uses a metal nanofilm instead of metal nanoparticles, thereby avoiding changes in the shape and pitch of metal nanoparticles due to laser irradiation, thereby improving the reproducibility and uniformity of the SERS substrate.
[0010] In addition, the SERS substrate of the present invention has an AAO substrate with a three-dimensional hole structure. The SERS substrate with extremely high detection ability can be obtained by the following mechanism. That is, compared with a substrate with a two-dimensional structure, a substrate with a three-dimensional structure has more hot spots distributed three-dimensionally due to the three-dimensional AAO holes, and the hot spots have higher intensity, so that the substrate with a three-dimensional structure can obtain higher sensitivity.
[0011] Specifically, one aspect of the present invention is An AAO substrate having a three-dimensional pore structure; and a metal nanofilm on the AAO substrate. This is a SERS substrate without metal nanoparticles.
[0012] The three-dimensional pore structure comprises a structure having nano-sized pores in micron-sized or nano-sized depressions, or a structure having nano-sized tips around the nano-sized pores, and the metal film is formed to adhere to the shape of the three-dimensional pore structure.
[0013] In some embodiments, the average pore size of the micron-order recesses in the three-dimensional pore structure is 0.1 to 5 μm, preferably 0.3 to 2 μm, and more preferably 0.5 to 1.5 μm, which can cause multiple reflections and amplify the Raman signal by causing more photons to inelastically collide with the probe molecules on the SERS substrate.
[0014] In some embodiments, the average roughness of the AAO substrate is 0.1-2 μm, preferably 0.4-1 μm, and more preferably 0.8-1 μm. Compared with two-dimensional substrates that reflect most of the incident light, the roughness of the AAO substrate can increase the inelastic collisions between photons and the tip molecules on the SERS substrate, thereby amplifying the Raman signal.
[0015] In some embodiments, the thickness of the metal nanofilm is 6 to 30 nm, preferably 10 to 20 nm. By using a metal nanofilm instead of metal nanoparticles, changes in the shape and pitch of metal nanoparticles due to laser irradiation can be avoided, and the uniformity, reproducibility, and uniformity of the SERS substrate can be improved, and localized surface plasmon resonance occurs, improving the sensitivity to the test object and enabling SERS measurement using the AAO substrate.
[0016] In some embodiments, the nanopores have an average pore spacing of 10-300 nm, preferably 10-100 nm. By reducing the average pore spacing of the nanopores, the intensity of the hot spots formed from the three-dimensional pore structure of the AAO substrate can be improved, thereby enhancing the Raman signal.
[0017] In some embodiments, the SERS substrate has a detection limit for methylene blue of at least 1×10 -10 This can be applied to industries that require water quality testing and prevent the damage caused by water pollution.
[0018] In some embodiments, the SERS substrate has a detection limit of as low as 0.05 ppm for melamine, which can be applied to detect residual melamine since the World Health Organization's recommended residual standard is 1 ppm or less.
[0019] Furthermore, the present invention provides a method for fabricating a three-dimensional pore structured AAO substrate free of metal nanoparticles using a special electrochemical processing process, which not only simplifies the process but also avoids the use of complex, costly and time-consuming acid wet etching and lithography processes in semiconductor processing, thereby reducing environmental pollution.
[0020] Specifically, the present invention changes the surface structure of an aluminum foil by subjecting the aluminum foil to an electrochemical treatment in an electrolyte solution at a specific temperature range, and forms a three-dimensional pore structure. The specific temperature range is 15 to 25°C, and preferably 15 to 20°C.
[0021] Thus, one aspect of the present invention is (A) a cleaning step of cleaning the aluminum foil; (B) a first electrochemical treatment step in which the aluminum foil is subjected to an electrochemical treatment with a direct current of 5 to 40 V in an electrolyte at 15 to 25 ° C. to change the surface structure of the aluminum foil; (C) a second electrochemical treatment step, in which the aluminum foil is further electrochemically treated with a composite pulse square wave to obtain an AAO substrate; (D) plating a single layer of metal on the surface of the AAO substrate to form the metal nanofilm; A method for manufacturing a SERS substrate. A three-dimensional pore structure is formed by performing the first electrochemical treatment step at 15 to 25°C. The detection intensity of the SERS substrate is improved by changing the surface structure of the AAO through a total of two electrochemical treatment steps.
[0022] Another aspect of the present invention is (A) a first electrochemical treatment step in which an aluminum foil is electrochemically treated with a direct current of 5 to 40 V in an electrolyte at 15 to 25 ° C. to change the surface structure of the aluminum foil; (B) a second electrochemical treatment step, further subjecting the aluminum foil to electrochemical treatment with a composite pulse square wave to obtain an aluminum foil structure having an AAO film; (C) a third electrochemical treatment step, in which the aluminum foil structure having the AAO film is subjected to an electrochemical treatment in a 5 wt % phosphoric acid electrolyte to obtain the AAO substrate; (D) plating a single layer of metal on the surface of the AAO substrate to form the metal nanofilm; A method for manufacturing a SERS substrate. A three-dimensional pore structure is formed by performing the first electrochemical treatment process at 15-25°C. The third electrochemical treatment process is a pore size enlargement process, which changes the surface structure of the AAO to enlarge the size of the nanopores in the three-dimensional pore structure and reduce the distance between the nanopores. This improves the detection intensity of the SERS substrate and enhances the Raman signal.
[0023] Another aspect of the present invention is (A) a first electrochemical treatment step in which an aluminum foil is electrochemically treated with a direct current of 5 to 40 V in an electrolyte at −20 to 20° C. to change the surface structure of the aluminum foil; (B) a second electrochemical treatment step, further subjecting the aluminum foil to electrochemical treatment with a composite pulse square wave to obtain an aluminum foil structure having an AAO film; (C) a third electrochemical treatment step, in which the aluminum foil structure with the AAO film is subjected to an electrochemical treatment in a mixed electrolyte of perchloric acid and ethanol to separate the AAO film and the aluminum foil, thereby obtaining the AAO substrate with nano-sized tips; (D) plating a single layer of metal on the surface of the AAO substrate to form the metal nanofilm; A method for manufacturing a SERS substrate. The three electrochemical treatment steps change the surface structure of the AAO, improving the detection intensity of the SERS substrate. The third electrochemical treatment step results in an AAO substrate with a three-dimensional pore structure with nano-sized tips, and the three-dimensionality of the three-dimensional pore structure in the AAO substrate is improved, resulting in an enhanced Raman signal.
[0024] Another aspect of the present invention is (A) a cleaning step of cleaning the aluminum foil; (B) a first electrochemical treatment step in which the aluminum foil is subjected to an electrochemical treatment with a direct current of 5 to 40 V in an electrolyte at 15 to 25 ° C. to change the surface structure of the aluminum foil; (C) a second electrochemical treatment step, further subjecting the aluminum foil to electrochemical treatment with a composite pulse square wave to obtain an aluminum foil structure having an AAO; (D) removing the AAO film by placing the aluminum foil structure having the AAO film in a mixed solution of phosphoric acid and chromic acid to remove the AAO film and obtain an aluminum foil having a surface structure; (E) a third electrochemical treatment step, in which the aluminum foil having the surface structure is electrochemically treated with a composite pulse square wave to obtain an AAO substrate; (F) a metal plating step of plating a single layer of metal on the surface of the AAO substrate to form the metal nanofilm; A method for manufacturing a SERS substrate. The AAO film removal step and the third electrochemical treatment step both adjust the morphology of the AAO substrate with a three-dimensional pore structure and improve the three-dimensionality of the three-dimensional pore structure of the AAO substrate, thereby enhancing the Raman signal. In addition, by performing the first electrochemical treatment step at 15 to 25°C, the surface structure of the aluminum foil is changed to obtain an AAO substrate with a three-dimensional pore structure, thereby improving the detection intensity of the SERS substrate.
[0025] In some embodiments, in the (C) second electrochemical treatment step, the aluminum foil is further subjected to electrochemical treatment for 3 to 5 minutes using a composite pulse square wave under the following conditions: Conditions: 0 to 40°C, phosphoric acid, oxalic acid, sulfuric acid, or a composition thereof is used as the electrolyte, the positive value of the pulse amplitude is 100 to 200V, the negative value is -2 to -8V, and the time ratio of the positive and negative pulses is 1:1 to 1:4. This step allows the formation of AAO, which can improve the detection ability of SERS. The voltage used varies depending on the type of acid. Phosphoric acid: the positive value is 100 to 200V, and the negative value is -2 to -8V. Oxalic acid: the positive value is 100 to 150V, and the negative value is -2 to -8V. Sulfuric acid: the positive value is 10 to 60V, and the negative value is -2 to -4V. Effect of the Invention
[0026] By using a metal nanofilm, the SERS substrate of the present invention forms a structure in which surface plasmon resonance occurs, thereby preventing changes in the shape and pitch of metal nanoparticles due to laser irradiation and improving the stability, reproducibility, and uniformity of the SERS substrate.
[0027] The SERS substrate of the present invention is an AAO substrate with a three-dimensional hole structure obtained through a special electrochemical processing process, which allows multiple reflections to occur when irradiating a laser, and more photons are generated and collide inelastically with the probe molecules on the SERS substrate, thereby enhancing the intensity of the Raman signal, thereby solving the disadvantage of the poor sensitivity of the two-dimensional AAO substrate.
[0028] The manufacturing method of the SERS substrate of the present invention solves the drawbacks of the conventional SERS substrate manufacturing, which is high cost and time-consuming, and can manufacture the AAO substrate quickly and at low cost, so that the AAO substrate can be disposed of without being reused after inspection. In addition, the simplified process is extremely advantageous for mass production.
[0029] The SERS substrate of the present invention has high sensitivity and stability, and can be applied to industries that require water quality testing, such as wastewater treatment and ecosystem protection. After collecting a sample outdoors, the sample can be directly dropped onto the SERS substrate and allowed to settle, and then after drying, a precise SERS test can be performed to analyze the types of substances contained in the sample and whether it meets international standards.
[0030] Screening of additives and detection of poor quality raw materials are important industries for ensuring food safety. By using the SERS substrate of the present invention, it is possible to directly and quickly test the types of ingredients contained in food and the presence or absence of illegal additives. In addition, the SERS substrate of the present invention has a low detection limit, so that illegal additives can be detected reliably. Furthermore, in the agricultural research industry, which analyzes pesticide ingredients and identifies varieties, the SERS substrate of the present invention can be used to detect the types and concentrations of pesticides remaining on the surfaces of vegetables and fruits, which greatly contributes to the management of illegal use of pesticides and restrictions on residual amounts of drugs.
[0031] The SERS substrate of the present invention can also be applied to the medical field where biomolecules such as cancer cells and DNA viruses need to be examined. For example, if a SERS database of different types of cells is created, the spectral distribution maps of normal cells and cancer cells can be distinguished by statistical analysis, and the spectrum of cancer cells can be inferred. Therefore, the SERS substrate of the present invention can be applied to fields such as drug screening and disease diagnosis. [Brief description of the drawings]
[0032] [Figure 1] is an SEM photograph of AAO-R5. [Diagram 2] is an SEM photograph of AAO-R15. [Diagram 3] is an SEM photograph of AAO-R20. [Figure 4] is a higher magnification SEM photograph of AAO-R20. [Diagram 5] 1 shows the SERS spectra of 10-5 M methylene blue measured on the SERS substrates having AAO-R5, AAO-R10, AAO-R15, and AAO-R20. [Figure 6] 1 shows the SERS spectra of methylene blue at various concentrations measured on a SERS substrate with AAO-R20. [Figure 7] 1 shows the SERS spectra of melamine at various concentrations measured on a SERS substrate with AAO-R20. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] The present invention produces a SERS substrate without metal nanoparticles by performing multiple electrochemical treatment steps using aluminum foil, particularly by performing electrochemical treatment on aluminum foil in an electrolyte at a specific temperature range. The substrate has an AAO substrate with a three-dimensional pore structure, the three-dimensional pore structure being a structure having nano-sized pores in micron- or nano-sized depressions leading to high roughness, or a structure having nano-sized tips around nano-sized pores, which can cause multiple reflections when irradiating a laser, and more photons are generated and collide inelastically with the probe molecule, thereby enhancing the Raman signal. In addition, since a single layer of metal is plated on the AAO substrate, localized surface plasmon resonance occurs. Therefore, the SERS substrate of the present invention has high stability, high reproducibility, excellent uniformity and high sensitivity.
[0034] The contents of the present invention will be described below through the embodiments. The embodiments of the present invention are for the purpose of enumeration, and do not limit the present invention to all specific environments, applications, or special methods described in the embodiments of the present invention. Therefore, the description of the embodiments is only for the purpose of explaining the object of the present invention, and does not limit the present invention.
[0035] Example 1 [Manufacturing]
[0036] 1. Cleaning process The aluminum foil was ultrasonically cleaned in acetone and deionized water for 5 min to remove surface particles and oily dirt, and the surface of the aluminum substrate was rinsed with deionized water and dried with nitrogen gas.
[0037] 2. First electrochemical treatment process Aluminum foils were electrochemically treated for 5 minutes with a direct current of 20 V in a mixed solution of perchloric acid and ethanol at temperatures of 5°C, 10°C, 15°C, and 20°C, respectively, to obtain aluminum foils R5, R10, R15, and R20 with three-dimensional pore structures having different surface structures. In addition, the applicant conducted multiple experiments and found that the uniformity of SERS deteriorated when the temperature was 25°C or higher, and therefore found that the preferred temperature was 20°C.
[0038] 3. Second electrochemical treatment process At 25℃, each aluminum foil was subjected to the second electrochemical treatment by one-step hybrid pulse anodization method (HPA for short) (equipment model: Jiehan 5000) to obtain the AAO substrates denoted as AAO-R5, AAO-R10, AAO-R15, and AAO-R20, respectively. The positive value of the pulse amplitude was 120V and the negative value was -4V. The electrolyte was 5wt% phosphoric acid, and the electrochemical treatment time was 180s.
[0039] 4. Metal plating process A platinum metal film with a thickness of about 15 nm was plated on the surface of the AAO substrate having a three-dimensional pore structure using a platinum sputtering device (model number: JEC-3000FC, JEOL) to produce a SERS substrate for SERS measurement. 〔analysis〕
[0040] 1. Roughness measurement of R5 to R20 using a staircase contour measuring machine (Kosaka Lab, ET3000) The average roughness of R5, R10, R15, and R20 were about 0.18, 0.48, 0.82, and 0.91 μm, respectively. This indicates that in the first electrochemical treatment process, the higher the temperature of the electrolyte, the faster the reaction, which leads to localized over-etching, resulting in more pronounced holes and depressions in the aluminum foil, and improving the three-dimensionality of the three-dimensional pore structure. In addition, the aluminum foils obtained by the first electrochemical treatment process performed at 15°C and 20°C had significantly higher average roughness than the aluminum foils treated at 5°C and 10°C.
[0041] 2. Observation of nanostructures in AAO using a field emission scanning electron microscope (HR-FESEM, JEOL JSM-7001) 1 to 3 are SEM images of AAO-R5, AAO-R15, and AAO-R20, respectively. First, in FIG. 1, the surface of AAO-R5 had few irregularities and the electric field was uniformly distributed. On the other hand, as shown in FIG. 2, a number of micron-order pores were clearly observed on the surface of AAO-R15, and the micron-order pores were larger in area and had higher color contrast (i.e., more pronounced three-dimensional structure) than those of AAO-R5. In addition, in Figure 2, the two circled areas are micron-class depressions and nano-class depressions, respectively. When observing the micron-class depressions seen in the upper circle, there was a color contrast, that is, a difference in height, and the multiple black dots in the depressions were nano-class pores. Therefore, it was found that the micron-class depressions seen in the upper circle were a three-dimensional porous structure consisting of several to several tens of nano-class pores. When observing the nano-class depressions seen in the lower circle, there was a similar color contrast, that is, a difference in height. The multiple black dots in the depressions were nano-class pores. Therefore, it was found that the nano-class depressions seen in the lower circle also had a three-dimensional porous structure consisting of several to several tens of nano-class pores. The above three-dimensional porous structure further improved the surface roughness. This phenomenon will be more evident in Figure 4 described below.
[0042] When the reaction temperature of the first electrochemical treatment step was further increased to 20°C, the number and size of the micron- and nano-level pits etched increased significantly, and the phenomenon of the pits gathering was observed, as shown in Figure 3. In this way, the three-dimensionality of the three-dimensional hole structure in the SERS substrate was significantly improved, which contributed to the occurrence of multiple reflections, and more photons were generated and inelastically collided with the probe molecules, thereby enhancing the Raman signal.
[0043] Figure 4 is a higher magnification SEM image of AAO-R20. From Figure 4, it can be more clearly observed that the three-dimensional pore structure in the AAO substrate had multiple nano-sized pores, as circled in Figure 4, among the micron-sized and nano-sized depressions. Thus, the AAO substrate made of aluminum foil with prominent holes and depressions has a three-dimensional pore structure, which contributes to the occurrence of multiple reflections and scattering phenomena, and can enhance the Raman signal during inspection.
[0044] 3. Measurement of pore spacing using Image J software Using software called Image J, the pore spacing between nano-sized pores in the micron-sized and nano-sized depressions of AAO-R5, AAO-R10, AAO-R15, and AAO-R20 was measured. The pore spacing is defined as the linear distance from the outermost periphery of a nano-sized pore to the outermost periphery of another nano-sized pore. As a result of the measurement, the average pore spacing of AAO-R5, AAO-R10, AAO-R15, and AAO-R20 was 100 to 300 nm.
[0045] 4. Measurement of Raman Spectrum The SERS substrates having AAO-R5, AAO-R10, AAO-R15, and AAO-R20 were used, and 10 -5 The Methylene Blue was measured. Platinum was plated on a smooth silicon substrate, and 0.1M methylene blue was dropped onto it as a control. The Raman spectra obtained in each measurement were compared, and the results are shown in Figure 5. The measurement results showed that a surface with high roughness and a three-dimensional pore structure with high three-dimensionality can provide a better detection effect.
[0046] As shown in FIG. 5, the Raman spectra measured using the SERS substrates having AAO-R5, AAO-R10, AAO-R15, and AAO-R20 and the Raman spectrum of the control group showed a peak at 1615 cm -1 The signal intensities at 100 nm and 150 nm were 4643, 10844, 40122, 48413, and 421, respectively. Therefore, it is evident that AAO-R15 and AAO-R20, which have prominent three-dimensional pore structures, can enhance the Raman signal, and the maximum value was nearly 100 times that of the control group.
[0047] 5. Detection limit of methylene blue Using the SERS substrate with AAO-R20, the concentration was 10 -6 M, 10 -7 M, 10 -8 M, 10 -9 M, and 10 -10The results of the SERS spectrum are shown in Figure 6. -10 Even in a methylene blue solution with a concentration of 1615 cm -1 The SERS substrate with three-dimensional pore structure showed a detection limit of at least 10 for methylene blue. -10 M, and it was found to have extremely high applicability.
[0048] 6. Melamine detection limit Using a SERS substrate with AAO-R20, melamine solutions with concentrations of 50 ppm, 5 ppm, 0.5 ppm, and 0.05 ppm were measured. The SERS spectrum results are shown in FIG. 7. From FIG. 7, it can be seen that even a melamine solution with a concentration of 0.05 ppm has a peak at 710 cm -1 A significant signal was observed in the three-dimensional pore structure, and the detection limit for melamine was as low as 0.05 ppm, which is far lower than the 1 ppm residual standard set by the World Health Organization, demonstrating that the SERS substrate has extremely high applicability.
[0049] Example 2
[0050] 1. Cleaning process The aluminum foil was ultrasonically cleaned in acetone and deionized water for 5 min to remove surface particles and oily dirt, and the surface of the aluminum substrate was rinsed with deionized water and dried with nitrogen gas.
[0051] 2. First electrochemical treatment process The aluminum foil was subjected to electrochemical treatment for 5 minutes in a mixed solution of perchloric acid and ethanol (4:1 to 1:4) at a temperature of 15 to 25°C with a direct current of 5 to 40 V to obtain an aluminum foil with a three-dimensional surface structure.
[0052] 3. Second electrochemical treatment process The aluminum foil was subjected to the second electrochemical treatment with a composite pulse square wave at 0-40°C to obtain a porous AAO film. The positive value of the pulse amplitude was 100-200V, and the negative value was -2--8V. The time ratio of the positive and negative pulses was 1:1-1:4. The electrolyte was 5wt% phosphoric acid, and the electrochemical treatment time was 180s.
[0053] 4. 3rd electrochemical treatment process Next, the composite pulse square wave was stopped, and the reaction was continued in the electrolyte for 0 to 60 min to obtain the AAO substrate.
[0054] 5. Metal plating process A metal film with a thickness of about 6–30 nm was plated on the surface of the AAO substrate to fabricate a SERS substrate for SERS measurement.
[0055] In this example, a three-dimensional pore structure was formed by performing the first electrochemical treatment process at 15 to 25°C. In addition, the morphology of the AAO substrate with a three-dimensional pore structure could be further adjusted by performing a pore size expansion process by the third electrochemical treatment process. The pore size expansion process is to expand the size of the nano-class pores in the three-dimensional pore structure and reduce the distance between the nano-class pores. As a result, the three-dimensionality of the three-dimensional pore structure in the AAO substrate was improved, and the Raman signal was enhanced. Specifically, the pore spacing between the nano-class pores after the pore size expansion process was measured using software called Image J. The pore spacing is defined as the linear distance from the outermost periphery of a nano-class pore to the outermost periphery of another nano-class pore. As a result of the measurement, the average pore spacing was 10 to 100 nm. This shows that the pore size expansion process by the third electrochemical treatment process reliably reduced the average pore spacing from 100 to 300 nm to 10 to 100 nm, improving the three-dimensionality of the three-dimensional pore structure of the AAO substrate.
[0056] Method 3
[0057] 1. Cleaning process The aluminum foil was ultrasonically cleaned in acetone and deionized water for 5 min to remove surface particles and oily dirt, and the surface of the aluminum substrate was rinsed with deionized water and dried with nitrogen gas.
[0058] 2. First electrochemical treatment process The aluminum foil was subjected to electrochemical treatment for 5 minutes with a direct current of 5 to 40 V in a mixed solution of perchloric acid and ethanol (4:1 to 1:4) at a temperature of -20 to 20°C, to obtain aluminum foil with an average roughness (Ra) of 0.05 to 1 μm.
[0059] 3. Second electrochemical treatment process The aluminum foil was subjected to a second electrochemical treatment with a composite pulse square wave at 0-40°C to obtain a porous AAO film. The positive value of the pulse amplitude was 100-150V, and the negative value was -2-8V. The time ratio of the positive and negative pulses was 1:1-1:4. The electrolyte was 0.1-3M oxalic acid, and the electrochemical treatment time was 5 minutes. Thus, an aluminum foil structure with an AAO film was obtained.
[0060] 4. 3rd electrochemical treatment process The aluminum foil structure with the AAO film was placed in a mixed solution of perchloric acid and ethanol (4:1 to 1:4) and subjected to a third electrochemical treatment with a direct current of 120 to 180 V for 30 s to separate the aluminum foil and the AAO film, thereby obtaining an AAO substrate with a three-dimensional tip.
[0061] 5. Metal plating process A metal film with a thickness of approximately 6–30 nm was plated on the surface of the tip of an AAO substrate with a three-dimensional tip to fabricate a SERS substrate for SERS measurement.
[0062] In this example, the AAO substrate with a three-dimensional nano-sized hole structure was obtained through the third electrochemical treatment process, which improved the three-dimensionality of the three-dimensional hole structure in the AAO substrate, thereby improving the detection intensity of the SERS substrate.
[0063] Method 4
[0064] 1. Cleaning process The aluminum foil was ultrasonically cleaned in acetone and deionized water for 5 min to remove surface particles and oily dirt, and the surface of the aluminum substrate was rinsed with deionized water and dried with nitrogen gas.
[0065] 2. First electrochemical treatment process The aluminum foil was subjected to electrochemical treatment for 5 minutes with a direct current of 5 to 40 V in a mixed solution of perchloric acid and ethanol (4:1 to 1:4) at a temperature of 15 to 20°C, to obtain aluminum foil with an average roughness (Ra) of 0.05 to 1 μm.
[0066] 3. Second electrochemical treatment process The aluminum foil was subjected to the second electrochemical treatment with a composite pulse square wave at 0-40°C to obtain a porous AAO film. The positive value of the pulse amplitude was 100-150V, and the negative value was -2-8V. The time ratio of the positive and negative pulses was 1:1-1:4. The electrolyte was 0.1-3M oxalic acid, and the electrochemical treatment time was 1-60 minutes. In this way, an AAO substrate was obtained.
[0067] 4. AAO film removal process The AAO substrate was placed in a mixed solution of phosphoric acid and chromic acid (1 to 4 wt % chromic acid and 3 to 10 wt % phosphoric acid), and the AAO film of the AAO substrate was removed to obtain an aluminum foil having a surface structure again.
[0068] 5. 3rd electrochemical treatment process The aluminum foil was subjected to the third electrochemical treatment with a composite pulse square wave at 0-40°C. The positive value of the pulse amplitude was 100-150V, and the negative value was -2-8V. The time ratio of the positive and negative pulses was 1:1-1:4. The electrolyte was 0.1-3M oxalic acid, and the electrochemical treatment time was 1-60 minutes. This resulted in an AAO substrate with large and small pores.
[0069] Metal plating: A metal film with a thickness of about 6–30 nm was plated on the surface of the AAO substrate to fabricate a SERS substrate for SERS measurement.
[0070] In this example, a three-dimensional pore structure was formed by performing the first electrochemical treatment step at 15 to 25° C. In addition, both the AAO film removal step and the third electrochemical treatment step were able to adjust the morphology of the AAO substrate with a three-dimensional pore structure and improve the three-dimensionality of the three-dimensional pore structure of the AAO substrate, thereby enhancing the Raman signal and improving the detection intensity of the SERS substrate.
[0071] From the above, it can be seen from the above description of the implementation method and the embodiments that the present invention has the following breakthroughs and advantages over the prior art:
[0072] By using a metal nanofilm, the SERS substrate of the present invention can avoid changes in the shape and pitch of metal nanoparticles due to laser irradiation, thereby improving the stability, reproducibility, and uniformity of the SERS substrate.
[0073] The SERS substrate of the present invention is an AAO substrate with a three-dimensional hole structure obtained by a special electrochemical treatment process. In particular, the surface structure of aluminum foil or AAO is changed by electrochemical treatment in a specific temperature range to produce an AAO substrate with a three-dimensional hole structure. This allows multiple reflections to occur when irradiating a laser, and more photons are generated and collide inelastically with the probe molecules on the SERS substrate, thereby enhancing the intensity of the Raman signal, thereby solving the disadvantage of the poor sensitivity of the two-dimensional AAO substrate.
[0074] The manufacturing method of the SERS substrate of the present invention solves the drawbacks of the conventional SERS substrate manufacturing, which is high cost and time-consuming, and can manufacture the AAO substrate quickly and at low cost, so that the AAO substrate can be disposed of without being reused after inspection. In addition, the simplified process is extremely advantageous for mass production.
[0075] The SERS substrate of the present invention has high sensitivity and stability and can be applied to industries requiring water quality testing, such as wastewater treatment and ecosystem protection, and agricultural research industries for analysis of pesticide ingredients and identification of varieties, as well as in fields such as drug screening and disease diagnosis.
Claims
1. an anodic alumina substrate having a three-dimensional pore structure; a metal nanofilm on the anodic alumina substrate; The three-dimensional pore structure is a structure having nano-sized pores in micron-sized or nano-sized depressions, or a structure having nano-sized tips around the nano-sized pores, and the metal nanofilm is formed so as to be attached to the shape of the three-dimensional pore structure; Surface-enhanced Raman scattering substrates without metal nanoparticles.
2. 2. The surface-enhanced Raman scattering substrate according to claim 1, wherein the average pore size of the depressions in the three-dimensional pore structure is 0.1 to 5 μm.
3. 2. The surface-enhanced Raman scattering substrate according to claim 1, wherein the average roughness of the anodic alumina substrate is 0.1 to 2 μm.
4. The surface-enhanced Raman scattering substrate of claim 1 , wherein the metal nanofilm has a thickness of 6 to 30 nm.
5. 2. The surface-enhanced Raman scattering substrate according to claim 1, wherein the nanopores have an average pore spacing of 10 to 300 nm.
6. The surface-enhanced Raman scattering substrate has a detection limit of at least 0.05 ppm for melamine, and a detection limit of at least 1×10 for methylene blue. -10 The surface-enhanced Raman scattering substrate according to any one of claims 1 to 4, wherein M is
7. A method for producing a surface-enhanced Raman scattering substrate according to claim 1, comprising the steps of: (A) a first electrochemical treatment step in which an aluminum foil is electrochemically treated with a direct current of 5 to 40 V in an electrolyte at 15 to 25° C. to change the surface structure of the aluminum foil; (B) a second electrochemical treatment step, further subjecting the aluminum foil to electrochemical treatment using a composite pulse square wave to obtain the anodic alumina substrate; (C) a metal plating step of plating a single layer of metal on the surface of the anodic alumina substrate to form the metal nanofilm; A method for producing a surface-enhanced Raman scattering substrate.
8. A method for producing a surface-enhanced Raman scattering substrate according to claim 1, comprising the steps of: (A) a first electrochemical treatment step in which an aluminum foil is electrochemically treated with a direct current of 5 to 40 V in an electrolyte at 15 to 25° C. to change the surface structure of the aluminum foil; (B) a second electrochemical treatment step, further subjecting the aluminum foil to electrochemical treatment with a composite pulse square wave to obtain an aluminum foil structure having an anodic alumina film; (C) a third electrochemical treatment step, which comprises subjecting the aluminum foil structure having the anodic alumina film to an electrochemical treatment in a 5 wt % phosphoric acid electrolyte to obtain the anodic alumina substrate; (D) a metal plating step of plating a single layer of metal on the surface of the anodic alumina substrate to form the metal nanofilm; A method for producing a surface-enhanced Raman scattering substrate.
9. A method for producing a surface-enhanced Raman scattering substrate according to claim 1, comprising the steps of: (A) a first electrochemical treatment step in which an aluminum foil is electrochemically treated with a direct current of 5 to 40 V in an electrolyte at −20 to 20° C. to change the surface structure of the aluminum foil; (B) a second electrochemical treatment step, further subjecting the aluminum foil to electrochemical treatment with a composite pulse square wave to obtain an aluminum foil structure having an anodic alumina film; (C) a third electrochemical treatment step, in a mixed electrolyte of perchloric acid and ethanol, is performed on the aluminum foil structure having the anodic alumina film, thereby separating the anodic alumina film from the aluminum foil, and obtaining the anodic alumina substrate having the nano-tip. (D) a metal plating step of plating a single layer of metal on the surface of the anodic alumina substrate to form the metal nanofilm; A method for producing a surface-enhanced Raman scattering substrate.
10. A method for producing a surface-enhanced Raman scattering substrate according to claim 1, comprising the steps of: (A) a first electrochemical treatment step in which an aluminum foil is electrochemically treated with a direct current of 5 to 40 V in an electrolyte at 15 to 25° C. to change the surface structure of the aluminum foil; (B) a second electrochemical treatment step, further subjecting the aluminum foil to electrochemical treatment with a composite pulse square wave to obtain an aluminum foil structure having an anodic alumina film; (C) removing the anodic alumina film by placing the aluminum foil structure having the anodic alumina film in a mixed solution of phosphoric acid and chromic acid to remove the anodic alumina film and obtain an aluminum foil having a surface structure; (D) a third electrochemical treatment step, in which the aluminum foil having the surface structure is electrochemically treated with a composite pulse square wave to obtain the anodic alumina substrate; (E) a metal plating step of plating a single layer of metal on the surface of the anodic alumina substrate to form the metal nanofilm; A method for producing a surface-enhanced Raman scattering substrate.
Citation Information
Patent Citations
Optical electric-field enhancement device
JP2012063293A
Surface enhanced raman scattering unit
JP2014037969A
Substrate of Surface Enhanced Raman Scattering and method thereof
KR1020160109626A
Surface-enhanced raman spectroscopy substrate, fixing jig, and production method for surface-enhanced raman spectroscopy substrate
WO2021141064A1
Method of manufacturing surface enhanced raman scattering substrate
TWI731600B